Sedimentary patterns in the Vinchina basin: interplay between compressional and transcurrent tectonism during the andean orogeny - Ciccioli, Patricia Lucia (2013)
The Nevados del Famatina, located in northwestern Argentina (Fig. 1), is one of the higher non-volcanic mountains belts in South America reaching up to 6200 m in height. Despite the fact that the uplift of the Nevados del Famatina was (and is) closely related to the Andean Orogeny, these mountains are located about 400 km from the Chile trench and up to 100 km from the main Andean Cordillera (Cobbold et al., 2007). The origin of the high and isolated Nevados del Famatina is related to a Neogene tectonic syntaxis due to the relationship between the left-lateral Valle Fértil wrench fault and the right-lateral Tucuman wrench fault (Rossello et al., 2011). The Vinchina Basin, a highly subsiding basin that accumulated more than 10,000 m of continental sediments during the Neogene developed between the magmatic arc, located in the Andean Cordillera, and the Famatina Mountain. The study of the sedimentary fill of the Vinchina Basin allows reconstructing not only the evolution of the magmatic arc (and its associated deformation) but also the timing and effect of the uplift of the Nevados del Famatina.